Najazd faraona Sziszaka/Szeszonka na Kanan. Relacja biblijna a źródła egipskie - Nowogórski, Przemysław (Saeculum Christianum. Pismo Historyczne, 2019)
In the twentieth year of his reign Pharaoh Sheshonq invaded Canaan. This expedition is described in the inscription on the Bubastite Portal in Karnak. However, in two places in the Bible there is information about the invasion of Pharaoh Shishaq to Judah (1 Kings 14:25 – 26; 2 Chronicles 12:1 – 12). Generally, in contemporary science, both descriptions are considered to be a report about the same event. Accurate analysis of both texts does not allow such an interpretation. It leads to two conclusions: the sources talk about two different military campaigns, and Shishaq and Sheshonq I are not the some person. There is a clear lack of coherence between the biblical text and the Egyptian inscription in a few places. The biblical description is more in the nature of midrash than the historical chronicle. Religious issues come to the first place, and historical ones remain in the background.